2022
DOI: 10.1155/2022/9463717
|View full text |Cite
|
Sign up to set email alerts
|

UBE2D1 and COX7C as Potential Biomarkers of Diabetes-Related Sepsis

Abstract: Patients with diabetes are physiologically frail and more likely to suffer from infections and even life-threatening sepsis. This study aimed to identify and verify potential biomarkers of diabetes-related sepsis (DRS). Datasets GSE7014, GSE57065, and GSE95233 from the Gene Expression Omnibus were used to explore diabetes- and sepsis-related differentially expressed genes (DEGs). Gene set enrichment analysis (GSEA) and functional analyses were performed to explore potential functions and pathways associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…This is in concordance with another study, which reported that COX7C is associated with venous thromboembolism via its ability to inhibit miR-200a-5p [26]. Moreover, a recent study presented COX7C as a biomarker for sepsis-related diabetes mellitus [27]. There is not much more reported on the relationship between COX7C and cancer pathogenesis suggesting importance of future studies to explore the implications of COX7C upregulation in CML.…”
Section: Discussionsupporting
confidence: 86%
“…This is in concordance with another study, which reported that COX7C is associated with venous thromboembolism via its ability to inhibit miR-200a-5p [26]. Moreover, a recent study presented COX7C as a biomarker for sepsis-related diabetes mellitus [27]. There is not much more reported on the relationship between COX7C and cancer pathogenesis suggesting importance of future studies to explore the implications of COX7C upregulation in CML.…”
Section: Discussionsupporting
confidence: 86%
“…UBE2D1, a CKD candidate, is inferred as a potential biomarker for diabetes-related sepsis by a machine-learning pipeline using public databases ( Wang et al , 2022 ). Diabetes is a known risk factor for CKD ( Shahbazian and Rezaii, 2013 ), hence, further supporting the candidacy of UBE2D1 for a CKD target as deduced herein.…”
Section: Resultsmentioning
confidence: 99%
“…UBE2D1, a CKD candidate predicted to function outside the known CKD pathways (Figure 8, Tables S31&S32), is inferred as a potential biomarker for diabetes-related sepsis by a machine-learning pipeline using public databases (Wang et al, 2022). Diabetes is a known risk factor for CKD (Shahbazian and Rezaii, 2013), hence, further supporting the candidacy of UBE2D1 for a CKD target as deduced herein.…”
Section: Resultsmentioning
confidence: 99%